A pedogeomorfologia em ambiente semiárido paraibano, Brasil - Rocha, Danielma Ferreira da (2023)
Pedogeomorphology is defined as the study of the soil-relief relationship under different aspects: conceptual, methodological, operational and/or scalar. In landscapes, soils and reliefs, evolve together, with mutual influences in this process, constantly, one influences the other in different ways, in greater or lesser intensity, depending on the environmental context, resulting in landscape implications and complex pedogeomorphological processes. Knowledge regarding the physical environment is essential to guide territorial planning policies, environmental preservation and recovery of degraded areas. The Brazilian semi-arid is considered a fragile region from an environmental point of view, due to the occurrence of torrential rains, long periods of more exposed soils, large thermal amplitudes, among others. The region still lacks scientific information that allows for a deeper understanding of its dynamics. The objective of this work was to carry out a pedogeomorphological characterization of the RPPN Olho d'água das Onças, located in the municipality of Picuí-PB, in the Brazilian semi-arid region. The geological substrate of the study area is associated with the Serra do Martins Sedimentary Formation (ENsm), with the occurrence of conglomerates, sandstones, siltstones, claystones and laterites. A bibliographical and cartographic review of the region under analysis was carried out. For the characterization of the RPPN, cartographic products were elaborated in a GIS environment, using the QGIS software. The ALOS-PALSAR satellite image was used as a basis. Products such as: MDE, slope map, hypsometry were elaborated and from this information the geomorphological map was made. Field work was carried out with collections of seven soil profiles, representing different geomorphological compartments. Five geomorphological units were identified in the area: i) tableland, ii) escarpment, iii) valley with flat bottom, iv) structural valley, and v) river plain. The pedogeomorphological characterization of the RPPN provides relevant information for future preparation of the Management Plan for the Conservation Unit. The identification of geomorphological units and associated soils enabled a better understanding of the potential and vulnerabilities of each sector. Areas with tableland and Oxisols (Latossolos) are the most appropriate for creating zones of intensive use. In turn, greater care must be taken with the edges of the tableland, with high declivity and associated with poorly developed soils